Working Towards a Framework for Governing Health Research in Nepal - Bhurtyal, Ashok; Pant, Suman; Dangal, Ganesh; Gyanwali, Pradip (Journal of Nepal Health Research Council, 2020)
Health research activities have advanced considerably in Nepal over the past several years. However, stakeholders’ confidence on scientific community is shaken as the latter failed occasionally in adhering to ethical principles. Nepal Health Research Council has exercised regulatory authority to control and support research works. However, much more is needed given the scale at which studies are being carried out. It is high time to conduct an analysis of the current situation followed by the development of an overarching framework to strengthen health research that facilitates a range of actions along the continuum of identifying information needs to translation of knowledge into policies and practices for ultimately improving people’s health. Keywords: Ethics; health research systems; knowledge management; research regulation